Evading the Boomerang Effect: Using the Grant-Back Clause to Further Generative Appropriability from Technology Licensing Deals - Laursen, Keld; Moreira, Solon; Reichstein, Toke; Leone, Maria Isabella (Organization Science, 2017)
Technology licensing agreements potentially can create future appropriability problems. Drawing on the appropriability literature, we argue that the inclusion of a grant-back clause in technology licensing agreements is an attempt to balance the gains from and protection of the focal firms’ technologies. We hypothesize that the closer the licensed technology is to the licensor’s core patented technologies, the more likely the licensing agreement will include a grant-back clause, while the closer the licensed technology is to the licensee’s core patent portfolio, the less likely the agreement will include a grant-back clause. We hypothesize also that technological uncertainty is a positive moderator in the decision to include a grant-back clause, if the licensed technology is close to either the licensee’s or the licensor’s core technologies. We employ a hierarchical nested decision model to test the hypotheses on a sample of 397 licensed technologies. This method allows us to model the choice to include a grant-back clause as nested in the decision about which technologies to license out. We find broad support for our theoretical arguments.